Identification and characterization of individual airborne volcanic ash particles by Raman microspectroscopy - Ivleva, Natalia P.; Huckele, Susanne; Weinzierl, Bernadett; Niessner, Reinhard; Haisch, Christoph; Baumann, Thomas (Analytical and Bioanalytical Chemistry, 2013)
We present for the first time the Raman microspectroscopic identification and characterization of individual airborne volcanic ash (VA) particles. The particles were collected in April/May 2010 during research aircraft flights, which were performed by Deutsches Zentrum für Luft- und Raumfahrt in the airspace near the Eyjafjallajökull volcano eruption and over Europe (between Iceland and Southern Germany). In addition, aerosol particles were sampled by an Electrical Low Pressure Impactor in Munich, Germany. As references for the Raman analysis, we used the spectra of VA collected at the ground near the place of eruption, of mineral basaltic rock, and of different minerals from a database. We found significant differences in the spectra of VA and other aerosol particles (e.g., soot, nitrates, sulfates, and clay minerals), which allowed us to identify VA among other atmospheric particulate matter. Furthermore, while the airborne VA shows a characteristic Raman pattern (with broad band from ca. 200 to ca. 700 cm−1 typical for SiO2 glasses and additional bands of ferric minerals), the differences between the spectra of aged and fresh particles were observed, suggesting differences in their chemical composition and/or structure. We also analyzed similarities between Eyjafjallajökull VA particles collected at different sampling sites and compared the particles with a large variety of glassy and crystalline minerals. This was done by applying cluster analysis, in order to get information on the composition and structure of volcanic ash.